1986
DOI: 10.2118/14178-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mud Rheology on Annular Hole Cleaning in Directional Wells

Abstract: Summary The effects of field-measured mud rheological properties on cuttings transport in directional well drilling were studied experimentally. Water and bentonite/polymer muds were used, and angles of annulus inclination ranging from 0 to 900 from vertical. Experimental data were processed to express the cuttings transport quantitatively through annular cuttings concentration (vol%) at steady state. Three separate regions of hole inclination can be identified regarding cuttings transport: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 3 publications
1
69
0
4
Order By: Relevance
“…3a-d. As far as cuttings transport in highly deviated wells is concerned, researchers offer various ideas about the effect of viscosity on hole cleaning. Some researchers such as Zeidler (1972), Okrajni and Azar (1986), Pilehvari et al (1999), Jawad (2002), Kelessidis et al (2007) and Mohammadsalehi and Malekzadeh (2011) believe that raising viscosity of the drilling fluid deteriorates hole cleaning, because type of flow regime changes from turbulent flow to laminar flow; and it has been proved that cuttings can be better displaced in turbulent flow than laminar flow. On the other hand, there are also some investigators, for instance, Ford et al (1990), Iyoho and Takahashi (1993), Belavadi and Chukwu (1994), Shou (1999), Li et al (2004) who claim that improvement in hole cleaning occurs as viscosity increases.…”
Section: Effect Of Fluid Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…3a-d. As far as cuttings transport in highly deviated wells is concerned, researchers offer various ideas about the effect of viscosity on hole cleaning. Some researchers such as Zeidler (1972), Okrajni and Azar (1986), Pilehvari et al (1999), Jawad (2002), Kelessidis et al (2007) and Mohammadsalehi and Malekzadeh (2011) believe that raising viscosity of the drilling fluid deteriorates hole cleaning, because type of flow regime changes from turbulent flow to laminar flow; and it has been proved that cuttings can be better displaced in turbulent flow than laminar flow. On the other hand, there are also some investigators, for instance, Ford et al (1990), Iyoho and Takahashi (1993), Belavadi and Chukwu (1994), Shou (1999), Li et al (2004) who claim that improvement in hole cleaning occurs as viscosity increases.…”
Section: Effect Of Fluid Viscositymentioning
confidence: 99%
“…All lines give an upward trend by diverging from vertical, indicating that CTP has improved. Some researchers such as Okrajni and Azar (1986), Ford et al (1990), and Bilgesu and Chukwu (2007), believed that if hole angle increases, their negative influences on cutting transports will increase as well. However, the author believes that it also has some positive effects especially when the flow is laminar.…”
Section: Effect Of Hole Inclinationmentioning
confidence: 99%
“…Some of affective parameters on wellbore cleaning have been studied by some researchers experimentally (Tomren et al 1986;Yu et al 2004;Ford et al 1990;Hareland et al 1993;Okrajni and Azar 1986;Sifferman and Becker 1992;Hussaini and Azar 1983) and by modeling approach (Nguyen and Rahman 1998;Wazed 2002;Akhshik et al 2015;Zhu et al 2013). Tomren et al (1986) published the results of experimental studies with various drilling fluids in plastic pipe lines with inclination angle from 0° to 90°.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that for both muds with same rheological properties, water base mud has a better performance in the wells with 40°-50° inclination. Okrajni and Azar (1986) examined the effect of mud rheology on the annulus cleaning. The result of their experiments showed that mud rheology properties have a low effect on the cutting transport in turbulence flow, and in laminar flow, cutting transport is done better by increasing mud yield point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation